Investigation of superplastic behaviour in double-pass friction stir processed Mg–Al–Zn alloy - Deepika Harwani; Vishvesh Badheka; Vivek Patel (International Journal of Lightweight Materials and Manufacture, 2023)
Double-pass friction stir processing (FSP) engendered intense plastic deformation in Mg–3Al–1Zn alloy with variation in the most influential process parameters, namely tool rotation speed and tool traverse speed. The effect of change in the FSP processing route on the resulting grain size was also analysed. Uniformly distributed fine equiaxed grains (average grain size ∼ 6.15 μm) were acquired in the stir-zone (SZ) due to extensive dynamic recrystallization (DRX). Attainment of large grain refinement encouraged for further investigation of the alloy's superplastic behaviour at elevated temperatures. Microstructural examination was followed by uniaxial tensile tests that were carried out at three distinct temperatures of 350, 400 and 450 °C at the constant strain rate of 1.3 × 10−3 s−1. With the rising deformation temperature, reduction in the flow stress led to significant increase in the tensile elongations of all the processed specimens. Micro-grain superplasticity (elongation >200% under tension) was observed at the highest deformation temperature for the friction stirred specimen with the finest grains.